Arquivo e literatura: perspectivas de acesso e difusão da memória literária no Brasil - Cavalheiro, Marcos Ulisses [UNESP]; Rodriguez, Sonia Maria Troitiño [UNESP] (My University, 2013)
Besides storing, the culture and science institutions in charge of the of Brazilian writers’ personal archives play such an important role on the organization and representation of the country’s literary information. In general, the target public for these collections is composed by researchers from the field of Literature once the documents produced by the writers throughout his/her life and career constitute primary research source for the artistic, historical and literary investigation. However, it is still convenient to stand out those users with no academic instruction, whose interest in such collections is justified by their looking up to the individual. In this sense, literary memory places, such as the Brazilian Literature Archive Museum – AMLB (RJ) -, the Brazilian Literature Academy – ABL – (RJ) and the Brazilian Studies Institute – IEB – (SP) turn out to be responsible for offering access to the literary archives and literary information. Thus, it is necessary to consider that databases demonstrate themselves as utter disseminators of the preservation and diffusion of the literary memory, coming up with several possibilities for cultural and scientific action in Literature. This study focuses on showing the contributions of databases towards the literary archives, the challenges and perspectives observed according to the mentioned institutions’ reality, in whose missions the discourse of the literary memory preservation is inserted.

Para além do ato de custódia, as instituições de cultura e ciência responsáveis pelo recolhimento de arquivos pessoais de escritores brasileiros exercem papel sumo na organização e representação da informação literária. Em geral, o público usuário desses acervos são os acadêmicos do campo das Letras, à medida que os papéis acumulados pelos escritores ao longo de sua trajetória de vida e carreira constituem uma verdadeira fonte primária à investigação artística, histórica e literária. No entanto, ainda deve ser destacada a parcela dos usuários desprovida dessa instrução acadêmica, mas cujo interesse em tais arquivos se justifica por sua admiração e afinidades com o titular. É nesse sentido que esses lugares de memória literária, tais como o Arquivo-Museu de Literatura Brasileira AMLB (RJ), a Academia Brasileira de Letras – ABL (RJ) e o Instituto de Estudos Brasileiros – IEB (SP), assumem a responsabilidade de propiciar o acesso aos acervos e à informação literária. Nesse sentido, é preciso considerar que as bases de dados se apresentam como verdadeiros propagadores na preservação e difusão da memória literária, surgindo, assim, vastas possibilidades de ação cultural e científica em Literatura. Neste recorte, visamos apresentar algumas contribuições das bases de dados dos arquivos literários, os desafios e perspectivas observadas na realidade das mencionadas instituições, em cujas missões inserem-se o discurso da preservação da memória literária.
Archive and literature: perspectives on access and difusion of the literary memory in brazil